2008
DOI: 10.1021/ac801853r
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube−Ionic Liquid Composite Sensors and Biosensors

Abstract: A new composite electrode has been fabricated using multiwall carbon nanotubes (MWCNT) and the ionic liquid n-octylpyridinum hexafluorophosphate (OPFP). This electrode shows very attractive electrochemical performances compared to other conventional electrodes using graphite and mineral oil, notably improved sensitivity and stability. One major advantage of this electrode compared to other electrodes using carbon nanotubes and other ionic liquids is its extremely low capacitance and background currents. A 10% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
160
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(168 citation statements)
references
References 29 publications
1
160
0
3
Order By: Relevance
“…The sensor showed a linear range between 5 and 100 mM and a detection limit of 2 mM. Mixtures of colloidal gold modified graphite powder with a solid RTIL, n-octyl-pyridinium hexafluorophosphate, were combined with glucose oxidase to prepare paste electrodes (89,275,276). The proposed biosensor responded to glucose linearly over concentrations ranging from 5.0 mM to 2.6 mM, with a fast response (10 s), and the lifetime was reported to be over 2 months (275).…”
Section: Tailoring Nanocomposites For Biomedical Applicationsmentioning
confidence: 99%
“…The sensor showed a linear range between 5 and 100 mM and a detection limit of 2 mM. Mixtures of colloidal gold modified graphite powder with a solid RTIL, n-octyl-pyridinium hexafluorophosphate, were combined with glucose oxidase to prepare paste electrodes (89,275,276). The proposed biosensor responded to glucose linearly over concentrations ranging from 5.0 mM to 2.6 mM, with a fast response (10 s), and the lifetime was reported to be over 2 months (275).…”
Section: Tailoring Nanocomposites For Biomedical Applicationsmentioning
confidence: 99%
“…By combination of CNTs and RTILs, attractive nanocomposites could be obtained which are useful for the study of protein direct electrochemistry [8][9][10]. These nanocomposites show high sensitivity and good biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…These nanocomposites show high sensitivity and good biocompatibility. Different methods have been developed for fabricating CNTs/ RTILs nanocomposite-based biosensors including electrode modification by RTIL/CNTs/polymer, layer-by-layer selfassembly, CNTs/RTIL pastes, or dispersion of RTIL/CNTs [8].…”
Section: Introductionmentioning
confidence: 99%
“…Of the carbon-based nanofillers, carbon nanotubes (CNTs) make them highly attractive as advanced engineering composite electrodes with various binders such as, Nafion [1], ionic liquids (ILs) [2], and Teflon [3], due to their ability to promote the electron transfer reactions of important biomolecules, including glucose, organophosphate, or NADH. One of the most promising ways to prepare the composite electrode with using CNTs is to modify the electrode surface with the dispersed CNT in a suitable solvent because of the easy, fast, and versatile method, inducing a high sensitivity, fast response time, and low detection limit [4,5]. The improved performance of the biosensors with using these types of composite electrodes depended on the properties of the nanomaterials with attractive electrochemical and mechanical properties and the binders with compatibility at the interface between biomolecules and electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The use of exfoliated graphite nanoplatelets coated with Nafion by Lee et al showed that the nanocomposite electrodes provide the improved electron transfer reaction of glucose with a high sensitivity and fast response time [7]. In addition to graphene, ionic liquids (ILs) have been widely used as another important material in enhancing performance of the modified electrode as a binder for biosensor because of their electrochemical stability, low back ground current, and biocompatibility [5]. ILs in previous works showed that they are effective solubilizing agents for CNTs and graphene nanosheets via p -p interactions, exhibiting improved sensitive signal for the detection of various analytes such as organophosphate [2], glucose [4], and ascorbic acid [9].…”
Section: Introductionmentioning
confidence: 99%